PENENTUAN JARAK OBJEK PENGHALANG MENGGUNAKAN METODE PERHITUNGAN JARAK PIKSEL DARI HISTOGRAM PROYEKSI BERPANDUAN LASER GARIS - Wicaksono, Ageng; Setyawan, F. X. Arinto; Herlinawati, Herlinawati (Jurnal Informatika dan Teknik Elektro Terapan, 2022)
The rapid advancement of digital image processing technology is expected to facilitate human life in various aspects of life. This study aims to detect and determine the distance of a barrier object based on the detection of lines emitted by a line laser light beam using the Matlab programming language with the pixel distance calculation method. The pixel distance calculation method is used to detect lines in an image that is processed by looking at the consistency of the laser lines. This study uses a box as an object to determine the presence of obstructions from an image captured by a camera. In this study, the parameters of distance, camera angle, and line laser angle are used. Research data collection was carried out in the afternoon in a closed room with a light intensity of 10 lux. An object can be said to be a barrier if in an image there is a laser line that is broken or not at the same pixel position. However, if in an image there are consistent lines or no line changes, then the image can be said to have no barriers. Based on the evaluation of the distance accuracy calculation with data collection, it can actually be concluded that the distance accuracy when taking data is above 85%.